(untitled) (Automatyka/Automatics, 2013)
In this paper we describe SOAROAD (SOA Related Ontology of Architectural Decisions), which was developed to support eva- luation of architectures of information systems using SOA techno- logies. The main goal of the ontology is to provide constructs for documenting service-oriented architectures, however, it is designed to support future reasoning. Building the ontology we focused on the requirements of Architecture Tradeoff Analysis Method (ATAM) which was chosen as reference methodology for architecture eva- luation.